2020
DOI: 10.22146/jtbb.57681
|View full text |Cite
|
Sign up to set email alerts
|

Distribution record of <i>Musa borneensis</i> var. <i>sarawakensis</i> Becc. and <i>Musa campestris</i> var. <i>sarawakensis</i> Becc. in West Kalimantan, Indonesia

Abstract: Borneo Island has a large number of wild banana species. As a part of Borneo Island, West Kalimantan has limited information about the diversity of wild bananas. This research aims to update the record distribution of wild bananas from Bonti District of Sanggau Regency and to determine their morphological characteristics. Exploration method and resident information were used in this study. Two species of wild bananas have been identified and considered as new distribution records in West Kalimantan Province, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Telugu : Aratipandu Hindi : Kela Marathi : Keli Bangla : Kala Sanskrit : Kadal Tamil : Valai PHYTOCHEMICAL PROPERTIES: [8][9] The edible part of Musa acuminata provide energy, vitamins, minerals and other parts of plants are used in treatment of many diseases in traditional medicine. The phytochemical present in Musa acuminata contribute to their beneficial effects.…”
mentioning
confidence: 99%
“…Telugu : Aratipandu Hindi : Kela Marathi : Keli Bangla : Kala Sanskrit : Kadal Tamil : Valai PHYTOCHEMICAL PROPERTIES: [8][9] The edible part of Musa acuminata provide energy, vitamins, minerals and other parts of plants are used in treatment of many diseases in traditional medicine. The phytochemical present in Musa acuminata contribute to their beneficial effects.…”
mentioning
confidence: 99%
“…Recently, surveys of bananas in Indonesia continued to progress. For example, Sutanto et al (2016) reported banana diversity in eastern Indonesia, Hastuti et al (2019) recorded new wild M. acuminata in Sulawesi, Sunandar (2017) and Sunandar and Kurniawan (2020) reported the presence of M. balbisiana, the distribution of M. borneensis and M. campestris in Kalimantan. Genetic diversity based on molecular study also has been reported.…”
mentioning
confidence: 99%